1996
DOI: 10.1016/s0009-9236(96)90162-9
|View full text |Cite
|
Sign up to set email alerts
|

First-pass metabolism of midazolam by the human intestine*

Abstract: The in vivo intestinal metabolism of the CYP3A probe midazolam to its principal metabolite, 1'-hydroxymidazolam, was investigated during surgery in 10 liver transplant recipients. After removal of the diseased liver, five subjects received 2 mg midazolam intraduodenally, and the other five received 1 mg midazolam intravenously. Simultaneous arterial and hepatic portal venous blood samples were collected during the anhepatic phase; collection of arterial samples continued after reperfusion of the donor liver. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
319
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(338 citation statements)
references
References 24 publications
18
319
0
1
Order By: Relevance
“…It is known that CYP3A4 is present not only in the liver but also in the small intestine (Watkins 1994). Paine et al (1996) have reported that midazolam undergoes extensive intestinal metabolism and have suggested that this plays a major role in the firstpass metabolism of this drug. Therefore, the differential effects of carbamazepine on the Cmax of midazolam and alprazolam appear to be ascribable to the difference between the two drugs in the extent of first-pass metabolism, especially that in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that CYP3A4 is present not only in the liver but also in the small intestine (Watkins 1994). Paine et al (1996) have reported that midazolam undergoes extensive intestinal metabolism and have suggested that this plays a major role in the firstpass metabolism of this drug. Therefore, the differential effects of carbamazepine on the Cmax of midazolam and alprazolam appear to be ascribable to the difference between the two drugs in the extent of first-pass metabolism, especially that in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Equilibrium Dialysis-Equilibrium dialysis experiments were performed in 0.5-ml Plexiglass cells separated by a dialysis membrane (molecular mass cutoff 12-14 kDa) (33,34). 1 M GST (300 l) was dialyzed against an equal volume of 0.5-50 M GS-NBD in a 25°C horizontal shaker water bath.…”
Section: Methodsmentioning
confidence: 99%
“…The CYP3A4-dependent interaction by food-derived agents may be related to the high level expression of CYP3A4 in the small intestine, as well as its broad substrate specificity (Fujita 2004). It has been confirmed that role of intestinal metabolism is significantly greater than hepatic in the firstpass effect for some drugs, e.g., cyclosporine A and midazolam (Isin and Guengerich 2007;Kanazu et al 2005;Kotegawa et al 2002;Paine et al 1996). Even more than half a percent of orally administered cyclosporine A is metabolized by enterocytes (Hebert 1997).…”
Section: Introductionmentioning
confidence: 99%